Methods of forming elementary concepts of renewable energy sources in physics on the basis of interdisciplinary connections - Abdiev Umirbek Begmatovich; Karimova Anora (Genius Journals, 2021)
The article describes the possibilities of using the principle of interdisciplinary connection in the formation of knowledge, skills and competencies in renewable energy sources in physics education. Also, the results of pedagogical experiments on the teaching of "Elementary concepts of solar photovoltaics" are presented and analyzed.
Keywords: The article describes the possibilities of using the principle of interdisciplinary connection in the formation of knowledge; skills; Elementary concepts of solar photovoltaics; pedagogical